An Empirical Analysis of Environmental and Financial Performance of BSE 100 Companies - Bammi, Ruchika (Indian Journal of Finance, 2013)
India is one of the largest and fastest growing economies in the world; the large-scale growth of Indian industries resulted in placing India as the third biggest greenhouse gas emitter in 2011, behind only China and USA. Thus, with India’s this growth came the international pressure to mitigate the greenhouse gas emissions. Indian companies are taking a cue from global competition and are demonstrating an increased awareness and understanding with regards to the risks and opportunities climate change presents to their businesses. The present study examines the differences in the financial and market performance of BSE 100 companies with a difference in the emission levels. The study uses greenhouse gas emissions’ data in capturing the effect of environmental performance and constructs two industry balanced portfolios of low and high emission levels. The environmental performance is measured in terms of emission intensity, and the financial performance is measured in terms of PBDITA and ROCE, while market performance is measured as average market return.